The Zero Violence Brave Club: A Successful Intervention to Prevent and Address Bullying in Schools - Roca-Campos, Esther; Duque, Elena; Ríos, Oriol; Ramis-Salas, Mimar (Frontiers in Psychiatry, 2021)
Bullying among peers in schools is a growing problem affecting children and adolescents from an early age around the world. The consequences of bullying victimization in the emotional development of children and youth and in their academic achievement are adverse for them and for the rest of the school community, while its negative impact can extend into the mid and long run. The Zero Violence Brave Club is implemented in schools in the framework of the Dialogic Model of Violence Prevention, a successful educational action according to the INCLUD-ED project [Strategies for inclusion and social cohesion in Europe from Education] (6th Framework Program of Research of the European Commission). The Zero Violence Brave Club has managed to decrease peer bullying in schools through establishing and cultivating a culture of zero tolerance to violence in educational centers located in diverse socio-economic and cultural contexts. This evidence-based intervention is grounded in the principle that only the person who denounces violence suffered by a peer and takes a stand always on the side of the victim –and those who support her or him–, and against the aggressor can be considered brave. This article reports a qualitative study of the Zero Violence Brave Club as a successful intervention in seven schools in Spain. The schools are diverse in terms of public or private ownership, religious or lay background and population served (different proportions of cultural minorities and students with special needs), challenging the misconception that the impact of educational interventions depends on the context. Interviews were conducted with teachers in the schools who had been implementing the Zero Violence Brave Club in their class, using the communicative methodology of research. The results shed light on specific mechanisms through which the Zero Violence Brave Club prevents and responds to bullying in schools, such as emptying of social attractiveness any aggressive behaviors or attitudes. Benefits on mental health and psychological wellbeing are also reported.